Development and Validation of CRISPR Activator Systems for Overexpression of CB1 Receptors in Neurons - Di Maria, Valentina; Moindrot, Marine; Ryde, Martin; Bono, Antonino; Quintino, Luis; Ledri, Marco (Frontiers in Molecular Neuroscience, 2020)
Gene therapy approaches using viral vectors for the overexpression of target genes have been for several years the focus of gene therapy research against neurological disorders. These approaches deliver robust expression of therapeutic genes, but are typically limited to the delivery of single genes and often do not manipulate the expression of the endogenous locus. In the last years, the advent of CRISPR-Cas9 technologies have revolutionized many areas of scientific research by providing novel tools that allow simple and efficient manipulation of endogenous genes. One of the applications of CRISPR-Cas9, termed CRISPRa, based on the use of a nuclease-null Cas9 protein (dCas9) fused to transcriptional activators, enables quick and efficient increase in target endogenous gene expression. CRISPRa approaches are varied, and different alternatives exist with regards to the type of Cas9 protein and transcriptional activator used. Several of these approaches have been successfully used in neurons in vitro and in vivo, but have not been so far extensively applied for the overexpression of genes involved in synaptic transmission. Here we describe the development and application of two different CRISPRa systems, based on single or dual Lentiviral and Adeno-Associated viral vectors and VP64 or VPR transcriptional activators, and demonstrate their efficiency in increasing mRNA and protein expression of the Cnr1 gene, coding for neuronal CB1 receptors. Both approaches were similarly efficient in primary neuronal cultures, and achieved a 2-5 fold increase in Cnr1 expression, but the AAV-based approach was more efficient in vivo. Our dual AAV-based VPR system in particular, based on Staphylococcus aureus dCas9, when injected in the hippocampus, displayed almost complete simultaneous expression of both vectors, high levels of dCas9 expression, and good efficiency in increasing Cnr1 mRNA as measured by in situ hybridization. In addition, we also show significant upregulation of CB1 receptor protein in vivo, which is reflected by an increased ability in reducing neurotransmitter release, as measured by electrophysiology. Our results show that CRISPRa techniques could be successfully used in neurons to target overexpression of genes involved in synaptic transmission, and can potentially represent a next-generation gene therapy approach against neurological disorders.